ANALISIS POLA SEBARAN KEJADIAN LONGSORLAHAN DI KECAMATAN SOMAGEDE DENGAN SISTEM INFORMASI GEOGRAFIS - Nirwansyah, Anang Widhi (Department of Urban and Regional Planning, Diponegoro University, 2015)
Landslide is part of forming mechanism which dynamically changing. This aim of research is to identify spatial pattern of landslide occurences in Somagede district using field survey and GIS as tool of analysis. The surveys are focused on occurrence and footprint that can be identified. Based on that, there are 39 points of landslide occurences laid on 7 villages which have steep slope and very steep slope categories. Average neighbor analysis shows the clustering pattern of landslide in Somagede, where the value of Nearest Neighbor Ratio is 0.768496. This hypothesis is supported by the z-score value -2.77 and p-value 0.0057 which are statistically accepted.